Beauty and the beast - Emma Watson; Dan Stevens; Luke Evens; Kevin Kline; Jose Gad; Evan McGregor; Stanley Tucci; Audra McDonald; Spanish.Spanish.Spanish.; Walt Disney Pictures ([Burbank, California] : Disney, 2017)
The story and characters you know and loBe our guest at the enchanted 25th Anniversary celebration, universally acclaimed as one of Disney2s finest animated features and now honored in the Walt Disney Signature Collection. Join brave, independent Belle on the adventure of a lifetime as she sets out to rescue her father and finds herself in the castle of a mysterious beast. This timeless tale overflows with unforgettable characters and Academy Award6winning music (Best Song, Best Score, 1991)!.ve come to spectacular life in the live-action adaptation of Disney's animated classic Beauty and the Beast, a cinematic event celebrating one of the most beloved tales ever told.
Originally produced as a motion picture in 1991.
Wide screen 16x9.
Be our guest at the enchanted 25th Anniversary celebration, universally acclaimed as one of Disney2s finest animated features and now honored in the Walt Disney Signature Collection. Join brave, independent Belle on the adventure of a lifetime as she sets out to rescue her father and finds herself in the castle of a mysterious beast. This timeless tale overflows with unforgettable characters and Academy Award6winning music (Best Song, Best Score, 1991)!.Be our guest at the enchanted 25th Anniversary celebration, universally acclaimed as one of Disney2s finest animated features and now honored in the Walt Disney Signature Collection. Join brave, independent Belle on the adventure of a lifetime as she sets out to rescue her father and finds herself in the castle of a mysterious beast. This timeless tale overflows with unforgettable characters and Academy Award6winning music (Best Song, Best Score, 1991)!.
Music, Alan Menken.
Emma Watson, Dan Stevens, Luke Evens, Kevin Kline, Josh Gad, Evan McGregor, Stanley Tucci, Audra McDonald, Gugu Mbatha-Ray, Ian McKellen, Emma Thompson
MPAA rating: G.
Keywords: Love -- Drama; Love -- Juvenile films; Magic -- Drama; Magic -- Juvenile films; Ugliness -- Drama; Ugliness -- Juvenile films; Love -- Drama; Magic -- Drama; Ugliness -- Drama